Benarkah Relationship Quality Berdampak Terhadap Word Of Mouth? - Dina Mayasari Soeswoyo; Ivan Christopher (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2019)
ABSTRACT The high level of competition in the restaurant industry in the city of Bogor, makes industry players strive to develop the right marketing strategy to be able to maintain business continuity, increase revenue and number of guests. Not only maintaining the quality of food, drinks and services, but also need to think about other factors that can support their business. This study aims to describe the description of relationship quality and word of mouth in de’Leuit restaurant, which is one of Sundanese favorite restaurants in the city of Bogor. Besides that, it is also to analyze the impact or influence of the relationship quality on word of mouth. This research was conducted in June-July 2018, using a quantitative approach with linear regression analysis techniques. Data collection techniques used in this study through direct observation, questionnaires and literature studies. The results of the analysis indicate that the description of relationship quality and word of mouth in De'Leuit Bogor restaurants shows the average score included in the high or good category, and relationship quality in De 'Leuit Bogor restaurants have a positive impact on word of mouth with an impact of 20.1%.Keyword: relationship quality, word of mouth, positive recommendation, personal communication                                                                                                                                                                  ABSTRAK Tingginya tingkat persaingan usaha industri restoran di Kota Bogor, membuat para pelaku industri berupaya keras menyusun strategi pemasaran yang tepat untuk dapat menjaga kelangsungan usaha, meningkatkan pendapatan dan jumlah tamu. Tidak hanya menjaga kualitas makanan, minuman dan pelayanan, namun juga perlu memikirkan faktor-faktor lain yang dapat menunjang usahanya.  Penelitian ini bertujuan untuk mengetahui gambaran relationship quality dan word of mouth di restoran de’Leuit yang merupakan salah satu restoran favorit khas sunda di Kota Bogor. Disamping itu juga untuk menganalisis dampak atau pengaruh dari relationship quality tersebut terhadap word of mouth. Penelitian ini dilakukan di bulan Juni-Juli 2018, menggunakan pendekatan kuantitatif dengan teknik analisis regresi linear. Teknik pengumpulan data yang digunakan dalam penelitian ini melalui observasi langsung, penyebaran angket dan studi literatur. Hasil dari analisis menyebutkan bahwa gambaran relationship quality dan word of mouth di restoran De’Leuit Bogor menunjukan skor rata-rata yang termasuk dalam kategori tinggi atau baik, dan  relationship quality di restoran De’ Leuit Bogor berdampak positip terhadap word of mouth dengan memberikan dampak sebesar 20,1 %.Kata kunci: relationship quality, word of mouth, rekomendasi positif, komunikasi personal